Eskalasi Kekerasan Berbasis Gender Online Di Masa Pandemi: Studi Penanganan Kasus Pornografi - Hany Areta A; Hardiana Clarisa; Siti Chatlia Q (Lex Renaissance, 2021)
This legal research aims to optimize the handling of Non-Consensual Dissemination Of Intimate Images in the context of realizing a just law by revising the explanations of Article 4 paragraph (1) and Article 6 of the Pornography Law ("Pornography Law"), as well as Article 27 paragraph (1) Law on Information and Electronic Transactions (“UU ITE”). This study uses a normative approach to the literature study method. This research is a reaction to the wrong interpretation of the regulation because it often leads to multiple interpretations. This is reflected in the nomenclature of “personal interest” in the Elucidation of Article 4 paragraph (1) and Article 6 of the Pornography Law which does not have any concrete limitations regarding the rights possessed. In line with this, the formulation of "violating decency" in Article 27 paragraph (1) of the ITE Law also leads to inconsistencies in the handling of various NCII cases. The author concludes that the definition of the two formulations, as well as the types of video storage that fall into the category of personal interest must be elaborated. Indonesia can also look in the mirror with other countries that are able to handle NCII cases, namely Australia.Keywords: Covid-19 pandemic; KBGO; NCII; pornography law; IT lawAbstrakPenelitian hukum ini bertujuan untuk mengoptimalisasi penanganan Non-Consensual Dissemination Of Intimate Images  dalam rangka mewujudkan hukum yang berkeadilan dengan merevisi penjelasan Pasal 4 ayat (1) dan Pasal 6 Undang-Undang Pornografi (“UU Pornografi”), serta Pasal 27 ayat (1) Undang-Undang Informasi dan Transaksi Elektronik (“UU ITE”). Penelitian ini menggunakan pendekatan normatif dengan metode studi literatur. Penelitian ini merupakan reaksi atas penafsiran yang keliru terhadap pengaturan tersebut karena kerap menimbulkan multitafsir. Hal ini tercerminkan pada nomenklatur “kepentingan pribadi” dalam Penjelasan Pasal 4 ayat (1) dan Pasal 6 UU Pornografi yang tidak memiliki batasan konkrit mengenai hak yang dimiliki. Selaras dengan hal tersebut, rumusan “melanggar kesusilaan” pada Pasal 27 ayat (1) UU ITE juga mengarahkan pada inkonsistensi penanganan berbagai kasus NCII. Penulis menyimpulkan bahwa definisi dari kedua rumusan tersebut, serta jenis penyimpanan video yang termasuk dalam kategori kepentingan pribadi harus dielaborasikan. Indonesia juga dapat berkaca dengan negara lain yang mampu menangani kasus NCII, yaitu Australia.Kata Kunci: Pandemi COVID-19, KBGO, NCII, UU Pornografi, UU ITE